2007
DOI: 10.1002/jmri.21127
|View full text |Cite
|
Sign up to set email alerts
|

Gadobenate dimeglumine‐enhanced MR angiography: Diagnostic performance of four doses for detection and grading of carotid, renal, and aorto‐iliac stenoses compared to digital subtraction angiography

Abstract: Purpose:To determine the diagnostic performance of contrast-enhanced MR angiography (CE-MRA) with four doses of gadobenate dimeglumine for detection of significant steno-occlusive disease of the carotid, renal, and pelvic vasculature. Materials and Methods:Eighty-four patients with suspected disease of the renal (n ϭ 16), pelvic (n ϭ 41), or carotid (n ϭ 27) arteries underwent CE-MRA (3D-spoiled gradient-echo sequences) at 1.5T. CE-MRA was performed with gadobenate dimeglumine at 0.025, 0.05, 0.1, or 0.2 mmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…However, the concentrations of gadobenate dimeglumine needed to achieve the maximum signal were much lower than for gadoteridol. This behavior may explain the clinical observations of Schneider et al who demonstrated that increasing the dose of gadobenate dimeglumine to 0.2 mmol/kg had no SNR advantage over 0.1 mmol/kg for MRA of multiple vascular territories (12). Finally, it should be noted that despite the high longitudinal relaxivity of ferumoxytol (r 1 ¼ 15 s À1 mM À1 ), its high transverse relaxivity (r 2 *¼ 89 s À1 mM…”
Section: Discussionmentioning
confidence: 88%
“…However, the concentrations of gadobenate dimeglumine needed to achieve the maximum signal were much lower than for gadoteridol. This behavior may explain the clinical observations of Schneider et al who demonstrated that increasing the dose of gadobenate dimeglumine to 0.2 mmol/kg had no SNR advantage over 0.1 mmol/kg for MRA of multiple vascular territories (12). Finally, it should be noted that despite the high longitudinal relaxivity of ferumoxytol (r 1 ¼ 15 s À1 mM À1 ), its high transverse relaxivity (r 2 *¼ 89 s À1 mM…”
Section: Discussionmentioning
confidence: 88%
“…mine have been shown as deleterious in terms of image quality and diagnostic performance ( 9,47,48 ). Notably, a 0.1-mmol/kg dose of gadobenate dimeglumine provides similar image quality and contrast enhancement to that achieved with a double 0.2-mmol/kg dose of gadopentetate dimeglumine for contrastenhanced MR angiography of the renal arteries and abdominal aorta ( 26 ) and carotid arteries ( 27 ).…”
Section: Vascular and Interventional Radiology: Contrast Materials Commentioning
confidence: 99%
“…However, a drawback of contrast-enhanced MR angiography is insuffi cient contrast enhancement for accurate visualization and diagnosis if the contrast agent dose is too low (6)(7)(8)(9). This is particularly relevant in the peripheral runoff vasculature where vessels are smaller and highly susceptible to fl ow alterations in heavily diseased patients; it is also relevant if parallel imaging techniques are used because these techniques decrease the signal-to-noise ratio (SNR) ( 10 ).…”
Section: Patientsmentioning
confidence: 99%
“…Traditionally, renal MRA has been performed with both single (0.1 mmol/kg) and double (0.2 mmol/kg) dose ECCM. However, most studies have found a single dose to be sufficient [20,21] and to reveal less degradation from background parenchymal enhancement [22]. Despite this, double doses were still widely used clinically prior to the advent of nephrogenic systemic fibrosis (NSF), which has dramatically changed dosing of Gd-based ECCM in clinical MRA [23].…”
Section: Contrast Agentsmentioning
confidence: 99%